PENGEMBANGAN PERANGKAT PEMBELAJARAN KIMIA MODEL KOOPERATIF DENGAN PENDEKATAN INKUIRI UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS SISWA SMA - Nurkhasanah Nurkhasanah; Tukiran Tukiran; Wahono Widodo (JPPS (Jurnal Penelitian Pendidikan Sains), 2017)
This research is a research development of teaching materials a model cooperative with inquiry approach on chemistry learning sub-subject factors that affect the rate of reaction, including: syllabus, lesson plans, student worksheets, students book and assessment sheet. This research was conducted at SMAN 5 Tuban through three stages: 1) Development of teaching materials with the model Thiagarajan, 2) Validation of teaching materials, and 3) Field try out with design One Group Pretest-Posttest Design. The results of this study are: 1) Teaching materials arranged by using cooperative learning model with inquiry approach are declared valid to be used in learning; a) the results of validation toward teaching materials that had been developed have good category and it can be used in teaching learning process; b) The level of difficulty for teahing materials developed are low and easy to be understood; c) Readability of instrument is high and the materials easy to understand by student; 2) The teaching materials is effective to be used in learning process, supported by: a) Learning outcome (product) is increase of high categories, b) students critical thinking skills is increase of with high categories, c) students responded positively to the teaching materials developed, and 3) The teaching materials developed is practical to be used in learning process shown by; a) the lesson plan used is in good category; b) The students activities are  dominated by forms of inquiry activities, presentations, and group discussions. Based on the results of this research can be concluded that the teaching materials with cooperative learning model with inquiry approaches that have been developed fulfills the validity, effectiveness, and practical, feasible to implement to improving students' critical thinking skills. Penelitian ini merupakan penelitian pengembangan perangkat pembelajaran model kooperatif dengan pendekatan inkuiri pada pembelajaran kimia SMA sub pokok bahasan faktor-faktor yang mempengaruhi laju reaksi, meliputi: silabus, RPP, LKS, Buku Ajar Siswa, dan Lembar Penilaian. Penelitian ini dilaksanakan di SMAN 5 Tuban melalui tiga tahap, yaitu 1) Pengembangan perangkat pembelajaran menggunakan model Thiagarajan, 2) Validasi perangkat pembelajaran, dan 3) Uji coba lapangan dengan rancangan œOne Group Pretest-Posttest Design. Hasil dari penelitian ini adalah: 1) Perangkat pembelajaran model kooperatif dengan pendekatan inkuiri dinyatakan valid untuk digunakan dalam pembelajaran model kooperatif dengan pendekatan inkuiri; a) hasil validasi perangkat pembelajaran yang dikembangkan berkategori baik dan dapat diterapkan dalam kegiatan belajar mengajar; b) Tingkat kesulitan perangkat pembelajaran yang dikembangkan rendah dan mudah dipahami siswa; dan c) Keterbacaan perangkat pembelajaran tinggi dan materi mudah dipahami oleh siswa; 2) perangkat pembelajaran dinyatakan efektif untuk digunakan dalam proses pembelajaran, yang didukung oleh; a) Tes hasil belajar produk meningkat dengan kategori tinggi, b) Keterampilan berpikir kritis siswa mengalami peningkatan dengan kategori tinggi,  dan c) Siswa memberikan respon positif terhadap perangkat pembelajaran yang dikembangkan, dan 3) Perangkat pembelajaran yang dikembangkan bersifat praktis untuk digunakan dalam pembelajaran yang ditunjukkan dari; a) keterlaksanaan RPP dalam kategori baik; b) Aktivitas siswa didominasi bentuk-bentuk kegiatan inkuiri, presentasi, dan diskusi kelompok. Berdasarkan hasil penelitian dapat disimpulkan bahwa perangkat pembelajaran model kooperatif dengan pendekatan inkuiri yang telah dikembangkan memenuhi unsur kelayakan, keefektivan dan kepraktisan, sehingga layak diimplementasikan untuk meningkatkan keterampilan berpikir kritis siswa.